Pengaruh Roa, Roe dan Per Terhadap Harga Saham Pada Bank Tabungan Pensiun Nasional Tbk 2015-2021 - Anisa Fitri; Fazhar Sumantri; Elisabeth Karamoy (Peneliti.net, 2022)
The purpose of this study was to determine the effect of ROA, ROE and PER on stock prices at the National Pension Savings Bank Tbk 2015-2021. The object of this research is ROA, ROE and PER on stock prices based on quarterly financial report data. The data source used is secondary data with time series data collection. The data collection technique was carried out by taking data through the Indonesian stock exchange site, to measure the magnitude of the influence of ROA, ROE and PER on stock prices at the National Pension Savings Bank Tbk 2015-2021 used multiple linear regression analysis techniques and classical assumption test using SPSS version Build 1.0 .0. 1447.